Prevalence and Risk Factors of Non-Alcoholic Fatty Liver Disease in Patients with Type 2 Diabetes Mellitus: A Cross-Sectional Study at a Tertiary Care Center - Sehrish Sheraz, Zeeshan Ghias Khan, Shuja Anwar Kazi, Fatima Hasan Kazmi, Nehal Shaikh, Aniqa Saleem, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Non-Alcoholic Fatty Liver Disease (NAFLD) is an emerging concern among patients with Type 2 Diabetes Mellitus (DM). This study was designed to evaluate the prevalence of NAFLD in Type 2 DM patients and to identify associated factors that may contribute to its occurrence. Methodology: Conducted in a tertiary care center's general medicine department from May 2020 to June 2021, this cross-sectional study enrolled 400 type-II diabetic patients, aged 35 years and above. Comprehensive interviews were performed to determine disease duration and medication usage and to exclude alternative causes of NAFLD. Physical examinations, including measurements of BMI and waist-hip circumference, along with abdominal ultrasonography, were utilized to detect and grade fatty liver. Results: The sample consisted of 217 females (59.8%) and 146 males (40.2%), with 67.2% having a diabetes diagnosis for over 10 years. NAFLD was identified in 69.1% of patients, more frequently in females (69%). A significant relationship was established between NAFLD occurrence and the duration of DM, BMI, and waist-hip ratio (p < 0.05). Conclusion: NAFLD was found in a striking majority of the diabetic population studied, approximately 70%, with a higher prevalence in females. Factors significantly linked to NAFLD incidence included the duration of diabetes and elevated measures of obesity and waist circumference. These findings underscore the need for heightened awareness and targeted interventions for this patient population. Keywords: Non-Alcoholic Fatty Liver Disease (NAFLD), Type-II Diabetes Mellitus (DM), prevalence, risk factors.